A Foolproof Method to Fabricate Integrated Electrodes with 3D Conductive Networks: A Case Study of MnOx@C‐Cu as Li‐Ion Battery Anode. Issue 3 (21st December 2016) - Cao, Kangzhe; Liu, Huiqiao; Chang, Xiaoya; Li, Yang; Wang, Yijing; Jiao, Lifang
Abstract : Integrated electrodes have attracted numerous attention for their wide applications, such as in battery, supercapacitor, and catalyst (for oxygen reduction reaction, oxygen evolution reaction, and hydrogen reduction reaction). When used for Li‐ion batteries, these electrodes always show superior electrochemical performance for their merits, such as binder free, open framework, and robust adherence. Nevertheless, the current integrated electrodes usually lack an effective conductive network or require a tedious postfabrication process. Herein, polyvinylpyrrolidone (PVP) is used as a bifunctional material, for its cohesiveness and ability of acting as N‐doping carbon precursor, to fabricate integrated electrodes with 3D conductive networks. Owing to its high N content (12.4 wt%), large volume shrinkage, and gas production, porous conductive network forms when PVP is carbonized. This strategy is foolproof, low cost, and can be scaled‐up. The electrodes fabricated by this method epitomize the merits of 3D conductive network, integrated structure, and open framework. As an example, MnO x @C‐Cu shows excellent electrochemical performance (1030 mA h g −1 at 0.4 A g −1 up to 350th cycles, and 320 mA h g −1 at 2.0 A g −1 ) when evaluated as Li‐ion battery anode owing to these merits. Moreover, other functional integrated electrodes are developed, paving an easy way to fabricate integrated electrodes with 3D conductive networks. Abstract : A scaled‐up foolproof method is developed to fabricate integrated electrodes with 3D conductive networks with the help of polyvinylpyrrolidone. It is low cost and environmentally friendly. The electrodes prepared in this method show superior electrochemical performances when evaluated as Li‐ion battery anodes. This method can be extended to the construction of other functional integrated electrodes, with the potential for extensive applications.